Pengaruh Konsentrasi dan Kemandirian Belajar Terhadap Hasil Belajar Peserta Didik Pada Mata Pelajaran Kimia Kelas X SMAN 15 Pekanbaru - Rahma Jusmini; Jimmi Copriady; Sri Wilda Albeta (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aims to determine the effect of concentration and learning independence on the chemistry learning outcomes of class X students of SMAN 15 Pekanbaru. This type of research is ex-post facto research with a quantitative approach. The population of the study was 157 students with 113 samples. The instruments used for data collection were questionnaires on learning concentration and learning independence. Data analysis in this study was a prerequisite analysis test and a hypothesis test. The results of the data analysis showed that in the F test the significance value was 0.000 <0.05, which means that there is an effect of learning concentration and learning independence on the learning outcomes of students in the chemistry subject of class X SMAN 15 Pekanbaru. In addition, in the t test of learning concentration, a significance value of 0.008 <0.05 was obtained, which means that there is an effect of learning concentration on the chemistry learning outcomes of class X students of SMAN 15 Pekanbaru and in the t test of learning independence, a significance value of 0.020 <0.05 was obtained, which means that there is an effect of learning independence on the chemistry learning outcomes of class X students of SMAN 15 Pekanbaru